1952
DOI: 10.1172/jci102625
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Potassium Deficit and Metabolic Alkalosis. The Pathogenic Significance of Operative Trauma and of Potassium and Phosphorus Deprivation 1

Abstract: Patients maintained postoperatively on parenteral fluids or a dietary intake low or lacking in potassium may develop a syndrome characterized by apathy, lethargy, muscular weakness, abdominal distension and ileus, cardiac arrhythmias and edema; and occasionally by confusion, delirium, muscular twitching and tetany. A clinical description of the syndrome as observed in 32 postoperative patients has appeared elsewhere (1). Evidence was found in these patients for the existence of potassium deficit, namely: 1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…With the administration of DCA the renal excretion of acid increased sharply above the expected level of excretion (Figure 2), the additional acid excretion being secondary to an increase in sodium reabsorption with an attendant increase in hydrogen ion secretion. Certainly in the presence of evidence of increased adrenal cortical activity very definite metabolic alkalosis may develop with modest potassium losses (32). A striking demonstration of the effect of DCA in precipitating metabolic alkalosis in the face of small potassium deficits and chloride loss was 1163 presented by Moore and associates (16), who suggested the importance of DCA in the blockade of renal correction of alkalosis.…”
Section: Discussionmentioning
confidence: 99%
“…With the administration of DCA the renal excretion of acid increased sharply above the expected level of excretion (Figure 2), the additional acid excretion being secondary to an increase in sodium reabsorption with an attendant increase in hydrogen ion secretion. Certainly in the presence of evidence of increased adrenal cortical activity very definite metabolic alkalosis may develop with modest potassium losses (32). A striking demonstration of the effect of DCA in precipitating metabolic alkalosis in the face of small potassium deficits and chloride loss was 1163 presented by Moore and associates (16), who suggested the importance of DCA in the blockade of renal correction of alkalosis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia stimulates renal ammonia 1 metabolism despite the frequent simultaneous occurrence of metabolic alkalosis (18,33,65,73). This is counterproductive from an acid-base homeostasis perspective, as increased ammonia excretion increases renal bicarbonate generation and can lead to further systemic alkalinization rather than to correction of the metabolic alkalosis that is often seen with hypokalemia.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality in glucose tolerance in ill subjects likewise is indicative of an alteration in carbohydrate metabolism well-known to occur in response to stressful stimuli (9,27,28,29). Hayes and Brandt (27) have shown that despite the impaired glucose tolerance curves seen in postoperative patients, the fall in serum phosphate is normal, a response which is comparable to that reported by Forsham and Thorn in subjects receiving ACTH or cortisone (26).…”
Section: Discussionmentioning
confidence: 60%